Faktor - Faktor yang Mempengaruhi Pengungkapan Aset Biologis Sesudah Penerapan PSAK 69 - Selvia Maya Suci; Fajar Gustiawaty Dewi; Sari Indah Oktanti Sembiring (Jurnal Akuntansi, Keuangan, dan Manajemen, 2022)
Purpose: This study aims to examine the effect of asset intensity, company size, KAP Big Four, public ownership, and profitability on disclosure of biological assets. Non-Cylical Consumer companies are the object of this study, and there are 48 data samples. Research Methodology: The testing technique used is purposive sampling, namely selecting samples with a particular model. In addition, the measuring tool used is SPSS 24. Result: Previous researchers showed, that the disclosure of biological assets is influenced by its intensity. In addition, company size has no effect on the disclosure of biological assets. Meanwhile, KAP Big Four has a significant and negative influence on the disclosure of biological assets. Furthermore, disclosure of biological assets is not affected by public ownership. implies that disclosure of organic resources will not be affected by open ownership. Profitability also has no effect on the disclosure of biological assets, so that profitability will not affect the disclosure of biological assets. Limitation: This study only uses the independent variables of biological asset intensity, company size, KAP Big4, public ownership, and profitability, and only uses the non-cyclical consumer sector listed on the IDX. Contribution: Companies, especially those that have gone public and are listed on the IDX, can benefit from this research. In addition, investors interested in investing can benefit from not only viewing the company's financial statements but also the disclosure of its biological assets for future research purposes. In this study, the variables, sample size, and population, and time of year were updated.